2022
DOI: 10.1155/2022/3602242
|View full text |Cite
|
Sign up to set email alerts
|

Plugging Performance of a New Sulfonated Tannin Gel System Applied in Tight Oil Reservoir

Abstract: In this study, based on the high-temperature characteristics of Western China tight oil reservoirs, a phenolic-larch tannin, temperature-resistant, plugging agent was synthesized by changing the mass fractions of larch tannin, double cross-linking agent, and accelerator. Young’s modulus of the dispersed gel was directly measured by an atomic force microscope, and the macroscopic plugging performance was evaluated by a physical simulation experiment of the artificially fractured natural core from Western China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…93,94 For natural polymer gel systems such as sulfonated tannin/formaldehyde/phenol, MnSO 4 , TiCl 4 , and tannin extracts can be selected to promote crosslinking reactions through complexation. 95 The rise of nanomaterials is of great significance. Liu et al 96 found that adding silica nanoparticles to PAM/HQ/HMTA helped accelerate gelation.…”
Section: Improved Gel Performancementioning
confidence: 99%
See 1 more Smart Citation
“…93,94 For natural polymer gel systems such as sulfonated tannin/formaldehyde/phenol, MnSO 4 , TiCl 4 , and tannin extracts can be selected to promote crosslinking reactions through complexation. 95 The rise of nanomaterials is of great significance. Liu et al 96 found that adding silica nanoparticles to PAM/HQ/HMTA helped accelerate gelation.…”
Section: Improved Gel Performancementioning
confidence: 99%
“…Cobalt complexes have unstable and reversible cobalt–carbon bonds in the presence of heat and light, which makes cobalt complexes suitable for long-term radical effects . The reduced transition metal (Fe, Cu, Ni) complexes induce homolytic cleavage of the carbon–halogen bond to form reactive free radicals, which initiates monomer polymerization. , For natural polymer gel systems such as sulfonated tannin/formaldehyde/phenol, MnSO 4 , TiCl 4 , and tannin extracts can be selected to promote cross-linking reactions through complexation . The rise of nanomaterials is of great significance.…”
Section: Improved Gel Performancementioning
confidence: 99%
“…Gel and foam systems, as the two most widely used plugging agents, have achieved positive progress in both laboratory experiments and field applications in recent decades [ 4 , 5 ]. Gel-based plugging systems have been used on a large scale in the 1990s, and various modified gels, micro-nano microspheres, polyethylene glycol gels (PEG), and chitosan-based gels have been developed, including preformed particle gel (PPG) and HPAM weak gels with various particle sizes and compositions [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%